Presentation_3_Antiviral protection in the Pacific oyster Crassostrea (Magallana) gigas against OsHV-1 infection using UV-inactivated virus.pptx - Benjamin Morga; Mickäel Mège; Nicole Faury; Lionel Dégremont; Bruno Petton; Jean-François Pépin; Tristan Renault; Caroline Montagnani (2024)
The increase of the frequency and severity of marine diseases affecting farmed marine mollusks are currently threatening the sustainability of this aquaculture sector, with few available prophylactic or therapeutic solutions. Recent advances have shown that the innate immune system of invertebrates can develop memory mechanisms allowing for efficient protection against pathogens. These properties have been called innate immune memory, immune priming or trained immunity. Previous results demonstrated the possibility to elicit antiviral immune priming to protect Pacific oysters against the ostreid herpes virus 1 (OsHV-1), currently plaguing M. gigas production worldwide. Here, we demonstrate that UV-inactivated OsHV-1 is also a potent elicitor of immune priming. Previous exposure to the inactivated virus was able to efficiently protect oysters against OsHV-1, significantly increasing oyster survival. We demonstrate that this exposure blocked viral replication and was able to induce antiviral gene expression potentially involved in controlling the infection. Finally, we show that this phenomenon can persist for at least 3 months, suggesting the induction of innate immune memory mechanisms. This study unravels new ways to train the Pacific oyster immune system that could represent an opportunity to develop new prophylactic strategies to improve health and to sustain the development of marine mollusk aquaculture.